Are school psychologists' special education eligibility decisions reliable and unbiased?: A multi-study experimental investigation. (December 2019) - Sullivan, Amanda L.; Sadeh, Shanna; Houri, Alaa K.
Abstract: Nearly 50 years of research show persistent racial disproportionality in the identification of special education disabilities, but the underlying mechanisms for these disparities remain largely unexplored. Because ambiguous regulations defining disabilities may allow subjectivity and unlawful differential treatment (i.e., racial bias or discrimination) in the special education eligibility process, an important target of study is disparate treatment of students by race in evaluations required to determine eligibility. School psychologists have long been recognized as highly influential in this process and in schools' resultant decisions. We used a 3 × 2 mixed factorial experimental design in three studies with simulated case report data to measure the influence of race and assessment data on school psychologists' perceptions of students' eligibility for special education in cases centering on emotional disturbance, intellectual disability, or autism, respectively. Participants included 302 practicing school psychologists in three states across the three experiments. There was little evidence of racial disparity, but participants tended to render decisions unsupported by, and even contrary to, evaluation data. Implications for research, practice, and professional development are discussed.